Improved Quality Parameter Estimation of Photovoltaic System Models based on SAO Algorithm - Attafi, Rim; Zitouni, Naoufal; Dashtdar, Masoud; Flah, Aymen; Elnaggar, Mohamed F.; Kanan, Mohammad (Engineering, Technology & Applied Science Research, 2024)
Solar energy provides one of the most favorable options regarding the transition to clean energy sources. The parameters of a photovoltaic (PV) system play determine its performance under various scenarios. The PV model parameter estimation is an example of nonlinear planning. This study proposes a novel use of the established Smell Agent Optimizer (SAO) algorithm to anticipate the undefined parameters of the PV model’s single-diode and two-diode equivalent circuits. This study aims to create a precise PV model that can accurately characterize its performance under changing operational conditions. The desired objective function is defined as the square of the mean squared error between the model’s current-voltage curve and the measured curve.